2022
DOI: 10.1007/s40145-022-0585-3
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of V2O5 and Bi2O3 on the grain boundary structure of high-frequency NiCuZn ferrite ceramics

Abstract: High-frequency soft magnetic ferrite ceramics are desired in miniaturized and efficient power electronics but remain extremely challenging to deploy on account of the power loss (Pcv) at megahertz frequencies. Here, we prepared NiCuZn ferrite with superior high-frequency properties by V2O5 and Bi2O3 synergistic doping, which proves to be a potent pathway to reduce Pcv of the ferrite at megahertz frequencies. The sample doped with 800 ppm V2O5 and 800 ppm Bi2O3 yielded the most optimized magnetic properties wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…E-mail: zhzhang@hdu.edu.cn, zhang@hdu.edu.cn highly resistive grain boundary segregation by TEM even at a low doping level (∼1000 ppm). 2,[34][35][36] There are also studies claiming the lattice substitution of Ca 2+ in spinel ferrites and the corresponding variation of magnetic properties. 20,[37][38][39][40][41][42] Therefore, the direct atomic-scale microscopic observation of Ca 2+ occupation in the spinel lattice is the premise of revealing its doping mechanism, which not only benefits the construction of ferrite theory, but also promotes the development of high-performance ferrite products.…”
Section: Institute Of Advanced Magnetic Materials College Of Material...mentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: zhzhang@hdu.edu.cn, zhang@hdu.edu.cn highly resistive grain boundary segregation by TEM even at a low doping level (∼1000 ppm). 2,[34][35][36] There are also studies claiming the lattice substitution of Ca 2+ in spinel ferrites and the corresponding variation of magnetic properties. 20,[37][38][39][40][41][42] Therefore, the direct atomic-scale microscopic observation of Ca 2+ occupation in the spinel lattice is the premise of revealing its doping mechanism, which not only benefits the construction of ferrite theory, but also promotes the development of high-performance ferrite products.…”
Section: Institute Of Advanced Magnetic Materials College Of Material...mentioning
confidence: 99%
“…Spinel structured ferrites (MFe 2 O 4 , M = Fe, Co, Ni, Mg…) refer to magnetic oxides that have the same crystal structure as the naturally formed MgAl 2 O 4 mineral. 1 They are widely applied in power electronics (transformers, inductors), [2][3][4] sensors, 5 catalysis, 6 magnetic imaging, 7 etc. due to their adjustable magnetic and physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] Segregation of dopant(s) to interfaces has a large importance to microstructures and properties of ceramics. [13][14][15][16] For instance, the grain growth behavior of Si 3 N 4 grains can markedly be altered by the addition of rare-earth dopants, such as La, Gd, and Lu. 17 Shibata et al observed that La dopants preferentially segregated to cation sites on the prism faces of β-Si 3 N 4 grains normally available for Si, effectively hindering the c-axis growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, Lorentz transmission electron microscopy has been utilized to visually characterize the magnetic domain structure of ferrite. [22][23][24][25][26][27] The distribution of domain walls can be shown by comparing the images in under-focused mode and over-focused mode. However, these static characterization results are difficult to directly establish a relationship with the dynamic core losses and a medium that can reflect the dynamic magnetization process, that is, the magnetic spectrum, is also needed.…”
Section: Introductionmentioning
confidence: 99%